Attention and Awareness: Evidence from Cognitive and Second Language Acquisition Research - Bandar Al-Hejin (Studies in Applied Linguistics & TESOL, 2004)
Over the past two decades, researchers in the field of second language acquisition (SLA) have become increasingly interested in the concept of attention. The role of attention has significant implications for theories of second language input, processing, development, variation, and instruction. Most of the literature on attention also addresses the concept of awareness. The two concepts are inherently connected but can be operationally distinguished. This review focuses on attention and awareness with respect to their definitions, theories, and the empirical evidence of their role in learning. Emphasis will be on research from cognitive psychology. This is followed by a brief review of SLA research relevant to Schmidt’s Noticing Hypothesis (1990). The discussion suggests that: (a) Schmidt’s definition of attention, as detection among other things, disregards the possibility of learning without attention; (b) attention facilitates SLA; (c) awareness is not necessary for converting input to intake; and (d) awareness can also facilitate SLA.